Desafios e possibilidades no fortalecimento da categoria profissional dos assistentes sociais em seus espaços sócio-ocupacionais: a experiência da Comissão de Orientação e Fiscalização (COFI) do CRESS/PR - Marco, Roberta Mischiatti de (2023)
The purpose of this study/research is to analyze the challenges and possibilities in strengthening the professional category of Social Workers in their socio-occupational spaces, based on the experience of the Guidance and Inspection Commission (COFI) of CRESS/PR. The motivation for this research came about during my time as a professional at the CRESS/PR COFI (2016-2019), when I realized that the commission's space represented a qualified research laboratory, full of content that dealt with the practice of social workers related to professional training and, at the same time, expressed impacts on the social and technical dimensions of collective work. The research process was based on a descriptive and analytical study, using qualitative and quantitative content from bibliographical, documentary and data research. The general objective was to analyze the professional demands of the different socio-occupational spaces received by COFI, in the period from 2007 to 2019. To achieve the general objective, we defined the following as specific objectives: Analyze the demands related to professional practice and ethical conditions and techniques identified in the documents; and identify the areas of professional activity corresponding to the object of the demands and the activities of CRESS based on Social Service legislation and regulations. Systematize the laws and regulations that guide the work of the CRESS/PR COFI. The research took place from the perspective of dialectical materialism, under the analysis of the data produced by the COFI of CRESS/PR, which analyzes the movement of the phenomenon analyzed within the totality. Knowing that the process of professional intervention presupposes recognizing the complexity of everyday life, from a perspective of totality, as well as the contradictory terrain on which professional actions are developed. Through this study/research, it was possible to see that the COFI plays a fundamental role for the profession by ensuring that, through the guidance and supervision of professional practice, the services offered respond to the demands of users with quality, based on reality and the legal apparatus available to the CFESS/CRESS Group.